2019
DOI: 10.1155/2019/5269074
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effect of Achillea fragrantissima against Adriamycin-Induced Cardiotoxicity in Rats via an Antioxidant and Anti-Inflammatory Pathway

Abstract: Adriamycin (Adr) is a cytotoxic anthracycline agent that is utilized to manage many types of tumors, but its clinical use is undesirable due to severe cardiotoxicity. The present study aimed to investigate the cardioprotective effect of Achillea fragrantissima (A. fragrantissima) against Adr-induced cardiotoxicity through the antioxidant and anti-inflammatory metabolic pathways. A single dose of Adr was injected in rats to induce cardiotoxicity. Rats are divided into 5 groups, control, A. fragrantissima 800, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…IL-6 is an important cardiac cytokine that is upregulated in the acute phase of cardiac injury [36], and mediates adverse myocardial remodeling [37]. Its elevated levels in relation with acute DOX-induced cardiotoxicity has been demonstrated in other studies [38,39]. Also, hsCRP is a strong indicator of cardiac stress that is accompanying increased rates of cardiovascular diseases [40].…”
Section: Plos Onementioning
confidence: 97%
“…IL-6 is an important cardiac cytokine that is upregulated in the acute phase of cardiac injury [36], and mediates adverse myocardial remodeling [37]. Its elevated levels in relation with acute DOX-induced cardiotoxicity has been demonstrated in other studies [38,39]. Also, hsCRP is a strong indicator of cardiac stress that is accompanying increased rates of cardiovascular diseases [40].…”
Section: Plos Onementioning
confidence: 97%
“…For example, the protective activities of various plant extracts of Phyllanthus amarus [ 10 12 ], Harungana madagascariensis [ 13 ], Carica papaya leaves [ 14 , 15 ], Zingiber officinale rhizome [ 16 – 19 ], Vernonia amygdalina leaves [ 20 , 21 ], and Garcinia kola seeds [ 22 , 23 ] against drug-induced hepato- and nephrotoxicities are well documented. Similarly, several studies have equally reported ameliorative effects of medicinal plants against drug-induced cardiotoxicity [ 24 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…After identifying certain substances, we did not find a proper match for a positive control. Moreover, recently published studies did not include positive controls [ 33 , 34 ]. Toxicity studies were not performed since methylxanthines have been well studied, and the doses used in the present study are significantly lower than the lethal doses of caffeine, theobromine, and theophylline in rats.…”
Section: Discussionmentioning
confidence: 99%